Time spent shopping and consumer clothing purchasing behaviour - Mihić, Mirela (Array, 2018)
The purpose of this study is to explore the impact of various antecedents and behavioural consequences of consumers’ perceptions of time spent on shopping for clothing products. Examined antecedent variables are gender, age, income, fashion consciousness and visual merchandising, while outcomes include the number of clothing items purchased. The data, collected by consumer survey in Croatia, was analysed using exploratory and confi rmatory factor analyses, and structural equation modelling (SEM). The major fi ndings indicate that visual merchandising has the greatest and positive effect on time spent shopping. As expected, women and younger consumers spend more time shopping than men and older consumers. As for the outcomes, shopping time is positively related to consumer purchases. The study was conducted at a single point in time and was carried out while there was still crisis in Croatia, in a situation where consumers spend less on fashion products. The present study provides the insights into the determinantsand consequences of time expenditure and might help fashion retailers design more successfully retailing strategies to encourage consumers to spend more time on shopping in fashion stores, which in turn leads to higher sales.